Field notes contributed by Paul Martsching, fall 1986 - Martsching, Paulet al (1986)
List of birds and locations contributed by Paul Martsching. The field notes include several bird descriptions. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1986. Epson - sheet feed